Religious Moderation in the Context of Islamic Economics in Indonesia: A Thematic Interpretation of al-Qur'an - Aidin Muhammad Fadly; Ahmad Yusam Thobroni; Muhammad Harisul Islam; Indika Ilwan Wahilmi (Taqaddumi: Journal of Quran and Hadith Studies, 2026)
Equitable economic welfare is not only a fundamental aspiration of society but also an important principle in Islamic teachings. However, this ideal has not yet been fully realized, as economic disparities in various regions continue to reflect unequal distribution of wealth and unequal access to economic opportunities. Such conditions indicate the need for stronger principles of social justice and balanced economic practices. In the Islamic perspective, these principles are closely related to the values of justice (‘adl), balance (tawazun), and concern for vulnerable groups (mustadh’afin) as taught in the Qur’an. Based on this framework, this study aims to elaborate the concept of religious moderation in achieving economic justice through the perspective of thematic Qur’anic interpretation. Using the maudhu’i (thematic) method of Qur’anic exegesis, this research collects and analyzes relevant Qur’anic verses comprehensively to formulate a conceptual framework of economic justice within the Indonesian context. Its implementation can be carried out through Islamic economic instruments such as zakat, almsgiving, and sharia-compliant trade, as well as religion-based social programs. The concept of religious moderation in economic affairs, as rooted in the Qur’an, offers a model for societal welfare development that adheres to the principles of Islamic economics. This approach not only presents technical economic solutions but also integrates moral and spiritual values in the pursuit of a fair and sustainable distribution of wealth.